Real world print production - McCue, Claudia (Peachpit Press, 2006)
Translating inspiration to the printed page has always been a challenge. The advent of desktop publishing granted new levels of power and control to the layout artist and graphic designer, but it hasn't eliminated the traditional pitfalls. In fact, it's introduced a few new ones. Sometimes managing the disparate elements of fonts, images, colors, and more, while dealing with the quirks of various layout applications makes even the bravest designer and production editor long for the hands-on days of moveable type. Creating a great layout on your monitor is only half the battle; how do you make it work on paper? Print production expert Claudia McCue takes on the challenge of putting ink to paper, offering clear, authoritative guidance to print professionals and anyone else who has been frustrated by the obstacles of getting electronic documents to print perfectly. In this book, you'll learn how to Get the most out of page layout programs such as Adobe InDesign and QuarkXPress, and decide which is right for your needs Use image applications such as Adobe Photoshop, Adobe Illustrator, and Macromedia FreeHand to reproduce the most complicated raster and vector images flawlessly Understand how ink and paper work together, and learn how to prevent unwelcome surprises in tricky situations such as overprinting, trapping, and color registration Use Adobe Acrobat to distribute your document in a universally accessible format while preserving your layout Wrangle your fonts, and choose the best ones from among the huge array of available typefaces Preflight, or prepare your job for submission to a printer or service bureau "Claudia offers a deadly combination of wit and wisdom. If you're involved with print, buy this book!"--David Blatner, co-author Real World InDesign CS2 and Real World Photoshop CS2.